The Influence of Work Discipline, Work Motivation, and Work Environment on Employee Performance at Indera Community Health Center, Central Java Province - Hayatun, Rahmi; Octavia, Ayu Nurafni (Economics and Business Solutions Journal, 2024)
This research aims to determine the influence of Work Discipline, Work Motivation and Work Environment on Employee Performance at the Community Sensory Health Center Office, Central Java Province. The sampling technique used a saturated sampling of 35 people. In this research, data was collected through questionnaires and data analysis tools using SPSS 27, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using the t-test, f-test and R2 test. The results of this research show that Work Discipline and Work Motivation have a significant effect on employee performance. In contrast, the Work Environment has no effect. It is not significant on employee performance, with coefficient of determination (Adjusted R Square) of 0.307 means that 30.7 percent of employee performance is influenced by the variables Work Discipline, Work Motivation and Work Environment. Meanwhile, the remaining 69.3 percent of employee performance was influenced by other variables not examined in this research